Detection of near-surface defects using a coin-tap approach based on the equivalent impact stiffness of Hertzian contact theory. (July 2023) - Chen, Dongdong; Huo, Linsheng; Song, Gangbing; Fan, Shuli
In this paper, a novel method to analyze the mechanical behavior of the coin-tap test using the principle of pounding mechanics is proposed. Based on the Hertzian contact theory, the linearized contact law is applied to simplify the mathematical model of the coin-tap test. By modeling the stiffness of the defect as an equivalent spring in a serial connection with the contact stiffness, the impact force and impact time can be theoretically derived. The derived expressions show that, the closer the defect is to the surface of the structure, the longer the impact duration time and the smaller the impact force will be. In addition, with the increase of defect radii, the peak force and duration of the impact will decrease and increase, respectively. Another innovation of this paper is that an equivalent impact stiffness (EIS)-based damage index (DI) is proposed to reveal the severity and location of the near-surface damages. Two validation experiments were carried out to validate the influences of the damage's radii and under-surface depths. In the first experiment, the impact force and time of the central point for eight plates are measured to validate the accuracy of the proposed model. In the second experiment, 18 points on the horizontal centerline of eight specimens were tapped at an interval of 1 cm. The recorded pounding force and time were processed by EIS-based DI. Experimental results show that the EIS-based DI can effectively predict the position and severity of the defects and it holds the potential for practical application.